(untitled) (Південний архів (історичні науки), 2023)
The research purpose is to characterize the image of Ukrainians in the territory of Southern Ukraine on the basis of the travelogues of foreign and Russian travelers of the late 18th – the first half of the 19th century. The methodological foundation of the research involves the methods of analysis, synthesis, frontier and local history. The main research findings. In the above-mentioned period of time in the territory of Southern Ukraine there were important geopolitical changes related to incorporation of the region into the Russian Empire. This event resulted in the movement of the Ukrainian population to Poltava, Chernihiv, Podillia, Volyn and other Ukrainian territories in order to colonize the South of Ukraine. As a consequence of these processes, Ukrainians settled in large territories of Southern Ukraine. These changes encouraged many people, among which there were Russians and foreigners, to evaluate such epochal events personally and describe them in their own travelogues. In the late 18th – the first half of the 19th century the region was visited by noblemen, merchants and scientists. The travelers left their travel notes (travel guides) which are a valuable source for the formation of the image of Ukrainians in the examined period of time in Southern Ukraine. Conclusions. In their travelogues, the visitors shared the impressions which could not be found in other types of historical sources. One of the major topics of the travelers’ notes was description of everyday life of the Ukrainian people. The disposition of Ukrainians living in Southern Ukraine took the central part in their descriptions. Due to those travel notes, it was possible to characterize disposition, lifestyle, activities, dreams and expectations of the local people, commercial and usurious deals etc. The research allowed identifying differences in the characteristics and evaluations of foreign and Russian travelers concerning the disposition and lifestyle of Ukrainians in the examined period of time.